2018
DOI: 10.1371/journal.pone.0197088
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcomes and predictors of response to photodynamic therapy in symptomatic circumscribed choroidal hemangioma: A retrospective case series

Abstract: BackgroundTo investigate the treatment outcomes and predictors of response to photodynamic therapy (PDT) in patients with symptomatic circumscribed hemangioma (CCH).MethodsThis retrospective case series examined 20 patients with symptomatic CCH (10 submacular CCHs and10 juxtapapillary CCHs) who underwent standard PDT (wavelength: 662 nm; light dose: 50J/cm2; exposure time: 83 sec) with verteporfin (6mg/m2), either as monotherapy (n = 9) or in association with other treatments (n = 11), of which 7 received intr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…PS photoactivation is a well-established therapeutic approach used to promote cell killing based on the interaction between visible light and matter [1,2]. The use of PS drugs in the clinic is termed “photodynamic therapy” (PDT), which is successfully targeted to cutaneous cancers, infections, and other pathologies [3,4,5,6,7]. In PDT, wavelength-selective light exposure of cells loaded with a PS promotes the inert PS molecule to a relatively long-lived excited state in which it interacts with molecular oxygen (O 2 ).…”
Section: Introductionmentioning
confidence: 99%
“…PS photoactivation is a well-established therapeutic approach used to promote cell killing based on the interaction between visible light and matter [1,2]. The use of PS drugs in the clinic is termed “photodynamic therapy” (PDT), which is successfully targeted to cutaneous cancers, infections, and other pathologies [3,4,5,6,7]. In PDT, wavelength-selective light exposure of cells loaded with a PS promotes the inert PS molecule to a relatively long-lived excited state in which it interacts with molecular oxygen (O 2 ).…”
Section: Introductionmentioning
confidence: 99%
“…Kwon et al [22] also reported that among those 5 patients 3 had sustained resolution for a mean 5.7 months and 2 patients showed recurrent serous macular detachment after 3 and 12 months, respectively [22]. However, Ho et al [8] reported in their retrospective study that although both the PDT monotherapy group (n = 9) and the group of PDT combined with intravitreal injection of bevacizumab (n = 7) showed effectiveness in improvement of visual acuity and in reduction of CFT for CCH; the PDT combined with IVB group did not show superiority on improving visual and anatomical outcomes compared to the PDT monotherapy group [8]. Our data is the first prospective clinical study to showed effectiveness of application of IVC as a primary treat- ment for exudative CCH both in maintaining BCVA and decreasing the mean CFT.…”
Section: Discussionmentioning
confidence: 97%
“…reported that in symptomatic cases a long-term poor visual acuity of 20/200 or worse was found in approximately 50% of patients if untreated [3]. Treatment modalities for symptomatic patients with CCH include photodynamic therapy (PDT) [6][7][8], laser photocoagulation [9,10], transpupillary thermotherapy (TTT) [11,12], external beam and proton beam radiation [13][14][15], gamma knife radiosurgery [16,17], and plaque brachytherapy [18,19]. However, all of these techniques have limitations, such as complications associated with radiotherapy (e.g., post-radiotherapy radiation retinopathy), impossibility to treat subfoveal lesions with laser photocoagulation or TTT, and tearing of of retinal pigment epithelium after PDT [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[16] Ho et al reported that patients presenting before the age of 50 years with pretreatment best-corrected visual acuity (BCVA) ≥ 20/200 and less foveal edema were most likely to benefit from PDT. [17] In a recent study by Di Nicola et al, investigating the predictive factors of visual outcome in 79 patients with CCH treated with PDT, the authors found correlations between good final visual outcome (≥20/40) and good baseline visual acuity, smaller tumor size, lack of CME, and lack of treatment prior to PDT. [18] With regards to the treatment parameters, double-dose PDT (12 mg/m 2 ) provided better tumor regression with similar resorption of SRF compared with standard-dose PDT (6 mg/ m 2 ).…”
Section: Circumscribed Choroidal Hemangiomamentioning
confidence: 97%